Experimental constraints on partial melting under UHT and dry conditions of quartzo-feldspathic rock in the Napier Complex, East Antarctica - Hokada, Tomokazu; Arima, Makoto (National Institute of Polar Research, 2001)
P(論文) We carried out high pressure melting experiments on a mixture of mineral separates of quartz, plagioclase (antiperthite) and a rare amount of orthopyroxene at 1000-1150℃ and 1.0 Gpa under dry conditions. The starting material was obtained from an ultrahigh-temperature (UHT) garnet-orthopyroxene-bearing quartzo-feldspathic gneiss in the Mt. Riiser-Larsen of the Napier Complex, East Antarctica. This UHT gneiss is considered to be equilibrated at metamorphic conditions >1070℃. The mineral assemblages in the run products at 1000℃ and 1100℃ are the same as those of the starting material. K_2O content in K-feldspar lamellae of antiperthite decreases with temperature. Granitic glass (<10 vol%) was detected along boundaries between lamella-free plagioclase and quartz grains in the run at 1150℃. The experimental results indicate that the homogenization temperature of this antiperthite lies <1150℃ at 1.0 Gpa. It is consistent with the estimated temperature from feldspar geothermometry. Major element composition of the glass at 1150℃ shows the molecular Al_2O_3/(Na_2O+K_2O+CaO) ratio (A.S.I.: aluminum saturation index) = 1.08 and high Na_2O+K_2O contents (8.1 wt%) relative to low CaO (1.3 wt%), which is comparable to the chemical features of A-type granite or leucogranite. This may imply that some genetic links might exist between UHT metamorphism and A-type granite magmatism in the Napier Complex. departmental bulletin paper